Does early specialization provide an advantage in physical fitness development in youth basketball? - Soares, André A L; Lima, Ahlan B; Miguel, Caio G; Galvão, Luciano G; Leonardi, Thiago J; Paes, Roberto R; Gonçalves, Carlos E; Carvalho, Humberto M (Frontiers in Sports and Active Living, 2023)
The present study examined the influence of the specialization onset on the magnitude and patterns of changes in basketball-specific physical fitness within a competitive season and developmental fitness trends between 11-17 years in young basketball players. Repeated measures of 181 young basketball players (female, n=40; male, n=141) were examined. Anthropometry, age, estimated maturity status, and basketball-specific physical fitness (assessed with the countermovement jump, line drill, and yo-yo intermittent recovery level-1 and fitness score) were considered. Players were grouped by the onset of specialization as related to biological maturation milestones (pre-puberty, mid-puberty, and late-puberty specialization). The within-season and developmental changes in physical fitness were fitted using multilevel modeling in a fully Bayesian framework. The fitness outcomes were similar between-player and within-player changes when grouped by specialization across a season. Fitness improvements across a season were apparent for female players, while male players maintained their performance levels. There was no variation in the patterns of physical fitness development between 11-17 years associated with the onset of specialization. Conditional on our data and models, the assumption that early sport specialization provides a physical fitness advantage for future athletic success does not hold.